2020
DOI: 10.1109/access.2020.3015808
|View full text |Cite
|
Sign up to set email alerts
|

Apple Bruise Grading Using Piecewise Nonlinear Curve Fitting for Hyperspectral Imaging Data

Abstract: Apple fruits can be easily damaged, and bruises occur on peels during harvest, transportation and storage, which could decrease fruit quality. This paper proposed an apple bruise grading method based on hyperspectral imaging (HSI). The spectral information of sound apples (Yantai Fuji 8) was first captured using a hyperspectral reflectance imaging device (386-1016 nm). These apples were then mechanically damaged by the same impact forces, and the bruised regions were exposed to room temperature for at most 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Scanning systems offer the advantage of producing images that can be easily extracted from raw data captured where high-speed acquisition is not required, for example, in agricultural measurements. Rapid data collection is often not necessary because vegetation changes over time scales of tens of minutes or hours [16]. Such systems are often attached to drones to produce hyperspectral images of large areas such as fields to assess characteristics of large numbers of plants simultaneously [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scanning systems offer the advantage of producing images that can be easily extracted from raw data captured where high-speed acquisition is not required, for example, in agricultural measurements. Rapid data collection is often not necessary because vegetation changes over time scales of tens of minutes or hours [16]. Such systems are often attached to drones to produce hyperspectral images of large areas such as fields to assess characteristics of large numbers of plants simultaneously [17].…”
Section: Introductionmentioning
confidence: 99%
“…Such systems are often attached to drones to produce hyperspectral images of large areas such as fields to assess characteristics of large numbers of plants simultaneously [17]. Lab-based systems are also used to assess individual plant properties, such as damage and/or deterioration in fruits and other fresh produce for non-destructive quality control and assessment [9,16]. Wider availability of low-cost, easy to operate systems that require minimal post-processing would enable better individual plant monitoring during growth and improved quality control in food distribution.…”
Section: Introductionmentioning
confidence: 99%
“…As the browning degree of the bruised area of samples increasing with the storage time, the browning degree changes more obvious at the beginning, the browning degree is close to the maximum value at 24 h, so that the browning degree doesn't change much at 48 h comparing with 24 h. Two distinct absorption valleys exist in all types of spectra. The absorption valley in the S1 region (680-720 nm) is caused by the chlorophyll in yellow peaches, the other in the S2 region (980-1020 nm) is caused by the O-H bond vibrations of water and sugar components (Tang et al 2020).…”
Section: Extraction and Analysis Of Features Extraction And Analysis ...mentioning
confidence: 99%
“…Based on raw data and pre-processed spectra, a partial least squares discriminant analysis (PLS-DA) classification model was established; then, various variable selection methods were used to select the feature variables; and finally, a PLS-DA model based on the feature variables was developed; the results showed that the hyperspectral imaging technology combining with PLS-DA could distinguish bruise's Lingwu long jujube at different storage times. Tang et al (2020) exposed the bruised area of the apple at room temperature for different periods, and spectral data of these samples were collected based on hyperspectral technology; then piecewise nonlinear curve fitting (PWCF) was used to extract the feature descriptors; finally, the feature descriptors were fed into an error correction output coding-based support vector machine (ECOC-SVM). The experimental results showed that the method effectively classified the storage time of bruised apples.…”
Section: Introductionmentioning
confidence: 99%
“…The selected features for training and testing the model include color, texture, and shape features. In [19], they proposed a piecewise nonlinear curve fitting (PWCF) procedure to maintain and present the spectral features of the hyperspectral images, and the error-correcting output code-based support vector machine (ECOC-SVM) was adopted to address the apple bruise grading problem. In [20], they utilized a Radio-frequency identification (RFID) tag as an electromagnetic transducer to convert the chemical-physical change of avocados into a modulation of the electromagnetic parameters when the avocados are ripening.…”
Section: Related Workmentioning
confidence: 99%